DETERMINAN KINERJA PEMBANGUNAN MANUSIA DI WILAYAH PASCA KAPET PAREPARE 2005-2012 - Syamsul Syamsul; Paulus Uppun; Madris Madris (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Humans are a national asset and base capital for the development of Indonesia. The aim of the research was tofind out to what extent the influence of government expenditure and private investment on human development performance. The research was conducted in the post area of KAPET of Parepare consisting of Barru Regerncy, Pinrang Regency, Sidrap Regency, Enrekang Regency, Parepare City. The date were secondary data analyzed using regression model of panel data. The results of the research indicate that government expenditure has influence on human development performance, while private investment influence human development performance. Government expenditure and private investment through economic growth have influence on human development performance.